Comparative study of land capability and land suitability for pepper plants (Piper nigrum L.) on karst and non-karst area in Pacitan Regency - Rahayu; Herawati Aktavia; Herdiyansyah Ganjar; Purwanto; Suyana Jaka; Adinda Friscilia Viska (BIO Web of Conferences)
Karst areas are often major challenges for agricultural development. Punung District in Pacitan Regency is included in the Gunung Sewu Karst Area, a UNESCO heritage geopark. Even as a center for pepper production, the production continues to decline. This study aims to determine the capability and suitability of land for pepper plants in the karst and non-karst areas of Punung District. This study is a field survey with purposive random sampling. The sampling points are based on the overlay of soil type, geology, and rainfall maps. The data variability of soil characteristics from the sampling was analyzed using ANOVA and resulted in a Land Map Unit (LMU). Data from the LMU were analyzed by matching the criteria for capability and land suitability with the results of observations. The results showed that the land capability of the karst and non-karst areas is the same class as II, III, and IV with limiting factors of surface, erosion rate, and soil depth. Land suitability for pepper is also the same, as marginal suitability (S3) with the limiting factors being the availability of water, very low available P nutrients, and the rate of erosion. The impact of this study is the Karst and non-karst do not significantly effect the class of land capability and land suitability for pepper plant development in this study area.